Explosion mitigation systems (FABIG technical note, 1994)
"The approach taken in this document is to try to explain, in a simplified manner, how a particular explosion mitigation system works. This is then built upon to describe the circumstances in which the mitigation method works and those circumstances where it will not work. Where possible, examples will be used to illustrate the concepts being explained. This document is intended to cover measures that may be taken to mitigate an explosion or its consequences. Since a number of these measures are activated on gas detection and prior to ignition, the document includes a qualitative discussion of gas detection. This will be in the context of actions that could be taken when gas is detected."--Knovel.